Profile of the main exogenous intoxications in the state of piauí: epidemiological analysis of a decade (Research, Society and Development, 2020)
The objective of this study was to describe the epidemiological profile of exogenous poisoning reported in Piauí - Brazil between 2007 and 2017, observing its impact on society. For this, a research with exploratory, epidemiological and descriptive appraisal with cross-sectional, quantitative and retrospective approach was developed, data collection was done on the DATASUS platform between these years, thus all available notifications were evaluated. The variables age, sex and toxic agent were studied, recording 8,210 reported poisoning cases. The results obtained with this research indicate that the sex most affected by poisoning is female 4879 notifications during this period and the most affected age is 20-39 years, with 3218 cases. Drugs are among the leading causes of poisoning 4023 records, highlighting a public health problem, and the rational use of medications. Thus, there is a need for campaigns, especially among young and female adults, related to suicide prevention in the state of Piauí, becoming more relevant work on this subject, helping to create public policies with the aim of reduction of this alarming number.